Pediatric optic neuritis: literature review - Bubnytė, S.; Andrulionytė, J. (Neurologijos seminarai, 2023)
Pediatric optic neuritis is an optic nerve inflammation occuring in 1 to 5 children out of 100,000 per year. In children, optic neuritis is rarely associated with multiple sclerosis, more often it can be associated with specific infections, such as diseases of the adjacent sinuses or orbital structures and infectious or infiltrative diseases of the brain or meninges, or it may develop as a separate pathological condition. This pathology is characterized by a sudden loss of vision, pain, especially associated with eye movements, and impaired color perception. It is diagnosed by performing visual function examination, morphological and radiological examinations. Optic neuritis is treated with corticosteroids, while pulse therapy can even speed up recovery in children from 7 to 2 weeks. The aim of this article is to review the symptoms, etiology, pathogenesis, diagnosis, treatment options, and prognosis of pediatric optic neuritis described in the literature.